Measuring disparities in out of hospital cardiac arrest outcomes in Chicago community areas - Marina Del Rios; Shaveta Khosla; Joseph Weber; Pavitra Kotini-Shah; Katie Tataris; Eddie Markul; Terry Vanden Hoek (Resuscitation Plus)
Background: Advances in resuscitation science have improved survival rates after an out-of-hospital cardiac arrest (OHCA) in select geographies, but survival rates vary widely by community. The purpose of this study was to assess the variations in bystander interventions and subsequent OHCA outcomes by predominance of a race/ethnicity within community areas in a large city. Methods: This is a retrospective cohort study of OHCA treated by Chicago Fire Department EMS from January 1st 2014 through December 31st 2021. Community areas were grouped into categories based on having a majority (>50%) of a race or ethnicity (i.e., predominantly White, Black, Hispanic, Integrated or Asian). Results: Of the 13,778 OHCA cases meeting inclusion criteria, 62.1% were male, and 47.5% were from predominantly Black community areas, 17.9% from predominantly Hispanic community areas, 20.0% from White, and 14.0% from Integrated; the remaining 0.6% were from Asian community areas. Mean age was lowest (59.9 years) in Hispanic followed by Black (61.8 years) community areas compared to White (62.4 years) community areas. Cases from Black and Hispanic community areas had lower rates of shockable rhythms (12.6% and 14.9% versus 19.8%). Bystander cardiopulmonary resuscitation (CPR) and automated external defibrillator (AED) use was lowest in Black community areas. OHCA in Hispanic and Black community areas > 30% less likely to have favorable neurologic survival compared to White community areas. Females were more likely to survive to hospital admission across all community areas; however, neurologic survival in females was better only in White and Integrated community areas. Public location and shockable rhythm were significant predictors of favorable neurologic survival across all community area categories; AED use before EMS was a significant predictor in Black, Hispanic and Integrated community areas but not in White community areas. Bystander CPR was associated with favorable neurologic survival White (aOR = 1.40) and Integrated (aOR = 2.02) community areas, but there was no significant association in Black or Hispanic community areas. Conclusion: Our study revealed significant variations in favorable OHCA characteristics across different community areas. While certain cardiac arrest features and modifiable factors play a significant role in some community areas, their effect may be less pronounced in other community areas.